2015
DOI: 10.1177/0284185114531128
|View full text |Cite
|
Sign up to set email alerts
|

pASL versus DSC perfusion MRI in lateralizing temporal lobe epilepsy

Abstract: pASL can successfully detect interictal asymmetry in patients with TLE and can readily be combined with routine structural assessment for lateralization, providing an alternative to DSC perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Blauwblomme et al further examined interictal cerebral perfusion deficits in children with focal cortical dysplasia by means of pCASL and FDG‐PET and reported concordance (i.e., colocalized abnormalities) in 5 of 6 (83%) cases . Recently, Oner et al evaluated ASL and DSC in detecting perfusion asymmetry for lateralization of seizure focus in refractory TLE (n = 36) and found similar asymmetry indices and similar correlations with clinical lateralization using the two imaging techniques . Details of these studies are presented in Table .…”
Section: Comparative Studies Between Asl and Pet/spect/dsc/dcementioning
confidence: 99%
See 3 more Smart Citations
“…Blauwblomme et al further examined interictal cerebral perfusion deficits in children with focal cortical dysplasia by means of pCASL and FDG‐PET and reported concordance (i.e., colocalized abnormalities) in 5 of 6 (83%) cases . Recently, Oner et al evaluated ASL and DSC in detecting perfusion asymmetry for lateralization of seizure focus in refractory TLE (n = 36) and found similar asymmetry indices and similar correlations with clinical lateralization using the two imaging techniques . Details of these studies are presented in Table .…”
Section: Comparative Studies Between Asl and Pet/spect/dsc/dcementioning
confidence: 99%
“…There are few ASL comparative studies in other neurological disorders such as epilepsy. It has been shown that ASL has a value in detecting perfusion deficits for localization or lateralization of seizure focus . In patients with drug‐resistant temporal lobe epilepsy (TLE) (n = 10), it was found that the mean CBF values in the mesial temporal lobe of ASL and 15 O‐water PET were not significantly different, ASL and FDG‐PET data were correlated and they were also correlated with the electrophysiological data (n = 3) .…”
Section: Comparative Studies Between Asl and Pet/spect/dsc/dcementioning
confidence: 99%
See 2 more Smart Citations
“…Despite the differences in techniques, both ASL and DSC have been used to lateralize temporal lobe epilepsy without the need for radioactive agents. 36…”
Section: Perfusion Imagingmentioning
confidence: 99%